Complete responses to odronextamab in two patients with diffuse large B‐cell lymphoma refractory to chimeric antigen receptor T‐cell therapy. (27th July 2022) - Weinstock, Matt; Elavalakanar, Pavania; Bright, Susan; Ambati, Srikanth R.; Brouwer‐Visser, Jurriaan; Pourpe, Stephane; Fiaschi, Nathalie; Jankovic, Vladimir; Thurston, Gavin; Deering, Raquel P.; Chaudhry, Aafia; Joyce, Robin; et al.
Summary: Outcomes remain poor for patients with relapsed/refractory B‐cell non‐Hodgkin lymphoma (R/R B‐NHL). While chimeric antigen receptor (CAR) T‐cell therapy has revolutionised treatment, a significant proportion of patients relapse or fail to respond. Odronextamab is a CD20 × CD3 bispecific antibody that has demonstrated durable responses and a manageable safety profile in patients with R/R B‐NHL in a first‐in‐human trial (NCT02290951). Here, we document two patients with diffuse large B‐cell lymphoma refractory to CART‐cell therapy. Both achieved complete responses that remain ongoing for ≥2 years following odronextamab. Neither patient experienced Grade ≥3 cytokine release syndrome or Grade ≥3 neurological adverse events during treatment.